Regional location of business sector research and development - Kent Eliasson; Pär Hansson; Markus Lindvert (Örebro University School of Business, 2024)
In the paper, we break down business sector R&D at an appropriate regional level (functional analysis regions, FA-regions) in Sweden. We describe the variation and development at the regional level. In an econometric analysis, we examine what affects the location and size of enterprise groups' R&D activities in different FA-regions. We find that enterprise groups concentrate their R&D to the same regions, which are also regions with significant academic R&D (external agglomeration). Moreover, colocation of R&D and manufacturing within an enterprise group in a region (internal agglomeration) appears to be a significant location factor. Last but not least, the local availability of qualified R&D labor is another important localization factor for business sector R&D. Finally, when we compare the results from the econometric analysis with what enterprise groups themselves states as important motives for location, we find that they match quite well.
Keywords: O32; R11; R12; J24; 330; business sector R&D; regional location; external agglomeration; colocation of R&D and production; abundance of qualified labor